Tindak Tutur Mengeluh Bahasa Jepang: Studi Kasus dalam Film Great Teacher Onizuka (2012) - Debby Rosiana Winoto; Bayu Aryanto (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2018)
This research was conducted to find out the forms of speech act and strategies of complaint in Japanese language. The data were taken from a Japanese drama, "Great Teacher Onizuka (2012)". They were then divided in to two categorize based on the types of complaint strategies performed by male and female protagonists. The researcher used descriptive qualitative method with pragmatic approach. The data were analyzed by using Anna Trosborgâ€™s (1995) theory of complaint strategies. Based on the research, the researcher found 8 complaint strategies, i.e. hints, annoyance, ill consequence, indirect accusation, direct accusation, modified blame, blame of the accusedâ€™s action and blame of the accused as a person. The researcher also found that gender differences affect the style of language when conveying the strategies of speech act of complaint.Â